Penerapan Nilai Adaptif Budaya Lokal Pada Pembelajaran PAI Di Sekolah Dasar Negeri Kota Bukittinggi - Gustina, Elvy; Hendri, Novi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research aims to explore the application of adaptive value of local culture in Islamic Islamic Religious Education (PAI) learning in public primary schools in Bukittinggi City. Bukittinggi. The method used is a qualitative approach with data data collection techniques through interviews, observation, and documentation. The results The results showed that the integration of local cultural values into the PAI curriculum not only improves students' understanding of the subject matter, but also strengthens their religious character rooted in local traditions. local traditions. The integration of local values, such as gotong royong, togetherness, and respect for the environment, in the PAI curriculum can increase students' motivation to learn. for the environment, in the PAI curriculum can increase students' learning motivation as well as their understanding of religious teachings. and their understanding of religious teachings. Through experiential learning methods, such as experiential learning methods, such as visits to cultural sites and direct engagement with the community, students not only learn theory but also with the community, students not only learn theory but also experience the application of these values in their daily lives. feel the application of these values in their daily lives. However, challenges such as limited resources and lack of training for teachers in integrating local wisdom into learning still need to be addressed. teachers in integrating local wisdom into learning still need to be addressed so that the application of these values can run optimally and sustainably. With the support of the community and related parties, it is hoped that local wisdom-based education can create a sustainable based education can create a generation that is not only academically smart but also has a strong character. academically but also have a strong character and are proud of their heritage. heritage. Implications